Exploration of the intercultural sensitivity of Primary Education students in schools of Aragon (Spain) - Orosia Campos, Iris; Lachén Iborra, Patricia (Didáctica. Lengua y Literatura, 2022)
Over the last two decades there has been a strong institutional commitment to foreign language teaching through educational models of integration of foreign content and languages (CLIL). This situation has focused research interest with studies centered mainly on the analysis of the effects of bilingual education on pupils’ academic performance. In the case of Aragon, although it is one of the Autonomous Communities at the forefront of CLIL models, there are no studies of this nature. In order to provide evidence of the potential impact of CLIL in Aragon, a quantitative study was carried out to explore the level of intercultural sensitivity of primary school pupils in bilingual schools. The research was carried out with 277 students in 4th, 5th and 6th grades of Primary Education. The results show a high level of intercultural sensitivity and the absence of differences according to variables that have been reported in previous studies, such as age, gender and the origin of the pupils and their parents. In addition, a positive correlation is found between the number of stays abroad and the level of intercultural sensitivity among children.